Comorbidity and severity of anxiety and depressive disordersin patients addicted to gambling and alcohol - Pyłypczuk, Aneta; Makara-Studzińska, Marta; Urbańska, Anna (Current Problems of Psychiatry, 2011)
Introduction. Addictions are disorders that are widespread in the world. At present, except for all the currently pervasive psychoactive substance addictions such as e.g. nicotine, alcohol, drugs, there are also more frequently occurring activity addictions, e.g. gambling, internet, shopping or sex, that are subjects of interest for many researchers [1].A few theses heretofore have documented the comorbidity of mental disorders and addictions. The phenomenon of cross-addiction also suggests that there are some common etiological factors that contribute to the development of more than one addiction. What is more, the comorbid mental disorders may play part in the persistence of addiction-related problems [2].The aim of this thesis was assessment of comorbidity and intensity of depression and anxiety in three groups of patients: two groups of those addicted to either alcohol or gambling and one of those addicted to both: alcohol and gambling.Material and method. The research was conducted in a group of 101 people, among whom 38 were addicted to alcohol, 31 addicted to gambling and 32 addicted to alcohol and gambling. All of the patients met the criteria of addiction to alcohol and pathological gambling according to ICD-10. Among the researched people there were patients of Circadian Ward of Alcohol Addiction Therapy in Lublin and members of the community of Anonymous Gamblers in Lublin. The research was conducted over the period from November 2010 to April 2011.Two scales: Hamilton Depression and Anxiety Rating Scale as well as the Scale of the intensity of anxiety, depression and stress DASS-42 were used in the research. In order to gather the socio-demographic data, an authorial questionnaire was used. The participation in the research was entirely voluntary and anonymous.Results. As a result of statistical analysis, it was stated that the symptoms of a major or a severe depression were insignificantly more frequent among the addicted to alcohol and gambling (48.39%) than among those addicted only to alcohol (23,68%) or gambling (25.00%). The ascertained differences however, were not statistically significant (p= 0.17).From the conducted research, it can be evaluated that anxiety symptoms on the level described as severe occurred more often in the group of alcohol addicts (44.74%) than in the group of those addicted to both alcohol and gambling (41.94%) and those addicted only to gambling (34.38%). The ascertained differences were not statistically significant (p= 0.12).As an outcome of the statistical analysis it was stated that stress symptoms were observed insignificantly more frequently in the group of gambling addicts (68.75%) than in the group of those addicted to both alcohol and gambling (64.52%) and alcohol addicts (44.74%). The ascertained differences were not statistically significant (p=0.09).The conducted research has shown that in the group of gambling addicts depression symptoms occurred insignificantly more often (78.13%) than in those addicted to both alcohol and gambling (74.19%) and those addicted only to alcohol (60.53%). The ascertained differences were not statistically significant (p=0.23).As a result of the statistical analysis it was stated that the intensity of anxiety had insignificantly greater incidence in the group of people addicted to both alcohol and gambling (41.94%) than in the group of those addicted only to alcohol (23.68%) and gambling addicts (28.13%). The ascertained differences were not statistically significant (p=0.24).Conclusions. The anxiety and depressive disorders are often comorbid with alcohol addiction and pathological gambling. Depressive disorders are a more frequent phenomenon in the group of pathological gamblers as well as in the group of those addicted to both alcohol and gambling and they are usually of either moderate or heavy intensity. The stress level is the highest in the group of patients addicted to gambling. There are some differences existing in the assessment of occurrence and intensity of anxiety in the researched groups. As it can be drawn from the conducted research, in the patients’ subjective assessment, the anxiety disorders are the rarest case among the alcohol addicts, whereas according to the clinicians’ assessment, there is the greatest incidence of them in this very group.